Comparación del valor nutricional del fruto de dos variedades charichuelo (Garcinia macrophylla, M.) de la Amazonía Peruana Iquitos – 2023 - Tomas Bazan, Carla Gehovanna (2024)
The research was aimed at comparing the nutritional values of the components present in the fruit of two varieties of charichuelo (Garcinia macrophylla, M.). The study was descriptive and comparative; we worked with two varieties from the Peruvian Amazon, which were collected in the markets of Belén and the city of Iquitos, where they are sold from the riverside towns. The study variables analyzed were: Humidity, ash, fat, fiber, proteins and carbohydrates, the results of which were expressed in percentages, nutritional value expressed in kilocalories and minerals such as calcium, magnesium, iron, sodium, potassium and zinc expressed in mg/100 g. , the same ones that show a higher percentage of carbohydrates (15.42% for the smooth charichuelo variety and 13.34% for the rough charichuelo variety), in terms of mineral content, sodium stands out (180.23mg/100g. for the smooth charichuelo variety and 160.30 mg/100g. for the charichuelo rugoso variety), followed by potassium (109.25 mg/g. for the charichuelo smooth variety and 102.5 mg/100g. for the charichuelo rugoso variety), also magnesium and calcium (95.20mg/100g, and 93.20mg/100g, respectively) for the smooth charichuelo variety and (85.5 mg/100g. and 81.30mg/ 100g, respectively) for the rough charichuelo variety. According to the values found for each variety, it is concluded that the smooth charichuelo variety presents lower values regarding its biometric properties and higher values regarding its nutritional components. The evaluations of the study variables in the two varieties of charichuelo were carried out in the laboratory of the Faculty of Chemical Engineering at the National University of the Peruvian Amazon.